2021
DOI: 10.1039/d0sc03695a
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic C–H to C–M (M = Al, Mg) bond transformations with heterometallic complexes

Abstract: C–H functionalisation is one of the cornerstones of modern catalysis and remains a topic of contemporary interest due its high efficiency and atom-economy. Among these reactions, C–H borylation, that is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 55 publications
0
29
0
Order By: Relevance
“…This side-reaction, which presumably follows a deprotonation-elimination pathway, strongly depends on metal size and becomes more important with decreasing metal size: Ba < Sr < Ca. Also for the tertiary 1-fluoro-adamantane SrN" 2 performed better than BaN" 2 (entries [16][17] and in this case no elimination side-products were observed. The [43,44] general reactivity trend is that conversion slows down in the order: primary > secondary > tertiary fluoroalkanes.…”
Section: Hydrodefluorination With Undefined Ae Metal Hydride Complexesmentioning
confidence: 78%
See 1 more Smart Citation
“…This side-reaction, which presumably follows a deprotonation-elimination pathway, strongly depends on metal size and becomes more important with decreasing metal size: Ba < Sr < Ca. Also for the tertiary 1-fluoro-adamantane SrN" 2 performed better than BaN" 2 (entries [16][17] and in this case no elimination side-products were observed. The [43,44] general reactivity trend is that conversion slows down in the order: primary > secondary > tertiary fluoroalkanes.…”
Section: Hydrodefluorination With Undefined Ae Metal Hydride Complexesmentioning
confidence: 78%
“…[11,12] Low-valent (BDI)Al I complexes can cleave the CÀ F bond in a ring with at least three F-substituents (Scheme 1b), requiring long reaction times and high temperatures, however, addition of catalytic quantities of Pd(PCy 3 ) 2 also allowed conversion of C 6 H 4 F 2 and C 6 H 5 F under mild conditions. [16][17][18] The mildest conditions (À 30°C) for CÀ F bond cleavage in C 6 H 5 F have been reported for a heterobimetallic Al I -Rh I complex. [19] We reported CÀ F bond cleavage in fluorobenzene using a Mg complex with a strongly reducing, anti-aromatic C 6 H 6 2À anion, but conditions were harsh (5 days, 100°C); Scheme 1c.…”
Section: Introductionmentioning
confidence: 99%
“…1 The use of aluminium-based metalloligands in catalysis is becoming increasingly popular, in part due to the abundance and low cost of this element. [2][3][4][5] For example, the inclusion of aluminium sites in pincer complexes of group 9 or 10 metals has led to new catalysts based on X-type aluminyl † metalloligands for alkane dehydrogenation, 6 the hydroarylation of alkenes with pyridine, 7 the magnesiation of aryl fluorides, 8 and the activation of CO2. [9][10][11] Related Z-type aluminium ligands have been shown to influence the catalytic competency of nickel metal-centres for alkene hydrogenation.…”
Section: Introductionmentioning
confidence: 99%
“…13,24,25 We have championed the catalytic applications of these types of complexes and suggested that dispersion interactions between the metalloligand and substrate can influence selectivity. 4,[13][14][15] In this paper, we report the synthesis of a series of eight new aluminylene complexes of 1 with first-row transition metals. These complexes have been characterised in the solid state and solution.…”
Section: Introductionmentioning
confidence: 99%
“…1 The use of aluminium-based metalloligands in catalysis is becoming increasingly popular, in part due to the abundance and low cost of this element. [2][3][4][5] For example, the inclusion of aluminium sites in pincer complexes of group 9 or 10 metals has led to new catalysts based on X-type aluminyl † metalloligands for alkane dehydrogenation, 6 the hydroarylation of alkenes with pyridine, 7 the magnesiation of aryl fluorides, 8 and the activation of CO2. [9][10][11] Related Z-type aluminium ligands have been shown to influence the catalytic competency of nickel metal-centres for alkene hydrogenation.…”
Section: Introductionmentioning
confidence: 99%